Green reduction of graphene oxide using alanine - ÇALIŞKAN SALİHİ, ELİF (ELSEVIER SCIENCE BV, 2017)
There remains a real need for the easy, eco-friendly and scalable preparation method of graphene due to various potential applications. Chemical reduction is the most versatile method for the large scale production of graphene. Here we report the operating conditions for a one-step, economical and green synthesis method for the reduction of graphene oxide using a biomolecule (alanine). Graphene oxide was produced by the oxidation and exfoliation of natural graphite flake with strong oxidants using Hummers method (Hummers and Offeman, 1958), but the method was revised in our laboratory to set up a safe and environmentally friendly route. The reduction of graphene oxide was investigated using alanine at various operatihg conditions in order to set up optimum conditions (treatment time, temperature and concentration of the reagent). Samples have been characterized by using UV-Visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscopy, Raman spectroscopy and X-ray diffraction analysis: (C) 2016 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).
Keywords: Graphene; Reduction; Biomolecule; Amino acid; Alanine; AMINO-ACID; CHEMICAL-REDUCTION; GRAPHITE OXIDE; VITAMIN-C; NANOSHEETS; WATER; NANOCOMPOSITES; CHEMISTRY; REMOVAL